Arsenic trioxide induces ferroptosis in neuroblastoma by mediating GPX4 transcriptional inhibition - Mingwei Su; Xiaoshan Liu; Yuhan Ma; Xiaomin Peng; Xilin Xiong; Wenjun Weng; Ke Huang; Yang Li (Wiley, 2024)
Abstract Neuroblastoma (NB), the most common extracranial solid tumor in childhood, significantly contributes to cancer‐related mortality, presenting a dearth of efficacious treatment strategies. Previously, our studies have substantiated the potent cytotoxicity of arsenic trioxide (ATO) against NB cells, however, the specific underlying mechanism remains elusive. Here, we first identified ATO as a novel GPX4 inhibitor, which could trigger the ferroptosis in NB cells. In vitro, ATO significantly inhibited the proliferation and migration ability of NB cells SK‐N‐AS and SH‐SY5Y, and induced ferroptosis. Furthermore, the iron chelator deferoxamine reversed ATO‐mediated intracellular reactive oxygen species accumulation and hindered the generation of the lipid peroxidation product malondialdehyde. Conversely, ferric ammonium citrate notably intensified its cytotoxic effects, especially on retinoic acid (RA)‐resistant SK‐N‐AS cells. Subsequently, the quantitative real‐time polymerase chain reaction results showed ATO significantly inhibited the transcription of GPX4 in NB cells. Remarkably, immunoblotting analysis revealed that MG132 exhibited a notable effect on elevating GPX4 levels in NB cells. Nevertheless, pretreatment with MG132 failed to reverse the ATO‐mediated decrease in GPX4 levels. These findings suggested that ATO reduced the GPX4 expression level in NB cells by mediating GPX4 transcriptional repression rather than facilitating ubiquitinated degradation. In conclusion, our research has successfully indicated that ATO could induce ferroptosis and initiate lipid peroxidation by regulating the transcriptional repression of GPX4, and ATO holds promise as a potential anti‐tumor agent in NB, specifically for patients with RA‐resistant HR‐NB.